EP268 Primary pelvic exenteration for advanced stages of pelvic cancers. (1st November 2019) - Capilna, ME; Moldovan, B; Fandi, A; Gheorghe, M; Kiss, SL; Stanca, M; Cozlea, AL
Abstract : Introduction/Background: The main indications for pelvic exenteration are recurrent or advanced pelvic malignancies. This radical surgical treatment that might be performed for some selected advanced gynaecological or urological cancers, without prior radio- or chemotherapy, is still controversial. Methodology: It is a retrospective study including 18 patients submitted to a primary pelvic exenteration between November 2011 and October 2018, with a mean age of 53.5 years. Regarding the pelvic malignancy, in 11 patients (61.1%), it was a stage IVa cervical cancer; a stage IVa vaginal cancer in 4 patients (22.2%); a stage IVa endometrial cancer in one and a bladder cancer stage IIIb in 2 patients. In all patients, the oncological contraindications were ruled out by MRI. Results: Out of 18 primary pelvic exenteration, 12 were anterior and 6 were total. Regarding the level of levator ani muscle, 10 exenterations were supralevatorian, 5 infralevatorian and 3 infralevatorian with vulvectomy. The reconstructive phase consisted in a Bricker urinary non-continent ileal or sigmoid conduit. There were no major intraoperative complications. Early complications occurred in 6 patients (33.3%) including a perioperative death (5.5%%) caused by a pulmonary embolism and 3 bowel fistulas (16.6%), in which a re-operation was needed. Only one patient has experienced a late complication - a urostomy stenosis which was solved. Among the 18 patients, at this moment, 12 (66.6%) are alive, 5 are dead because of the disease and one is lost to follow-up. Conclusion: Primary pelvic exenterantion in properly selected advanced pelvic cancers can be associated with long-term survival without high perioperative morbidity or mortality. However, postoperative complications can be lethal. Disclosure: Nothing to disclose.